A comparative study of the relative efficiency of different solvents used in softening guttapercha root canal filling material - Iman M Al-Zaka; Majidah K Al-Hashimi
This study was conducted to compare and evaluate the efficiency of four types of chemical solvents: Chloroform, Xylene, Orange Oil, and Eucalyptol Oil, in softening guttapercha and ZOE sealer. Forty extracted single-rooted premolar teeth were prepared using a step back technique and obturated with laterally condensed gutta-percha using ZOE as the sealer, then stored in 100% humidity at 37oC for 7 days. Specimens were randomly divided into four experimental groups based on the solvent to be used. A hedstrom file was used with a push-pull action to attempt penetration into the test samples. The addition of solvent was used to continue the penetration. The times taken for the hedstrom file to penetrate the length of the canals were recorded. The results showed that chloroform has statistically lowest mean of penetration time, followed by xylene, then orange oil. While eucalyptol oil has the highest mean of penetration time. No significant differences (p>0.05) were found between orange oil and xylene.